The Inequality in “Cewek!!!” and “Still…” - Anastacya Ruslim (Institute of Research and Community Outreach - Petra Christian University, 2018)
This study is about the main characters’, Langen, Febi, and Fani, effort in achieving equality in teen lit novels Cewek!!!and Still…,. However, despite the girls’ effort, they fail in achieving equality. To find the effort and failure of girls in achieving equality, I use the theory of gender stereotype. From the theory, I find that the girls show their effort in achieving equality from their strength, independence, logic, and intelligence. Although the girls show their effort, these novels still show the girls’ failure in achieving equality. It can be seen by the girls are pictured as weak, emotional, unintelligent, and submissive; while the boys (Rei, Bima, and Rangga) are pictured as strong, rational, and intelligent. In conclusion, I find that despite showing the girls’ effort, these novels also shows that the girls fail in achieving equality. Therefore, I hope that teen lit will have stories that do not judge girls, but shows real equality.